Aging is Neither a Failure nor an Achievement of Natural Selection - Carlos Aledo, Juan; Maria Blanco, Jose (Current Aging Science, 2015)
In contraposition to the view of aging as a stochastic time-dependent accumulation of damage, phenoptotic theories of aging postulate that senescence may provide supra-individual advantages, and therefore it might have been promoted by natural selection. We reason that although programmed aging theories are subjectively appealing because they convey a cure for aging, they also raise a number of objections that need to be dealt with, before we may be entitled to contemplate aging as an adaptive function evolved through natural selection. As an alternative view, we present metabolism as an endless source of by-products and errors causing cellular damage. Although this damage accumulation event is a spontaneous entropy-driven process, its kinetics can be genetically and environmentally modulated, giving place to the wide range of lifespans we observe. Mild forms of damage may be accumulating during a long enough period of time to allow reproduction before the fatal failure happens. Hence, aging would be a stochastic process out of the reach of natural selection. However, those genetic pathways influencing the rate of aging and consequently determining longevity may be targets of natural selection and may contribute to shaping the optimal strategy according to the ecological context. In this sense, short- and long-lived organisms represent two extreme strategies that, in terms of biological fitness, can perform equally well, each within its own niche.
Keywords: natural selection